Douglas Cater and Rufus W. Cater papers - Cater, Douglas; Cater, Rufus W.
Volume containing sixty letters addressed to a cousin, Fannie S. Cater, reflecting the soldiers' view of Confederate military losses at the battle of Shiloh (1862), siege of Vicksburg, Miss. (1863), Atlanta Campaign (1864), and battle of Nashville, Tenn. (1864).
Confederate army soldiers.
Collection material in English.
Keywords: Cater, Fannie S. -- Correspondence; Atlanta Campaign, 1864.; Nashville, Battle of, Nashville, Tenn., 1864.; Shiloh, Battle of, Tenn., 1862.; Georgia -- History -- Civil War, 1861-1865.; Mississippi -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Vicksburg (Miss.) -- History -- Siege, 1863.; Soldiers -- Confederate States of America